Competition for hydrogen by human faecal bacteria: evidence for the predominance of methane producing bacteria. Issue 12 (December 1991) - Strocchi, A; Furne, J K; Ellis, C J; Levitt, M D
Abstract : Studies of sludge have shown that some species of sulphate reducing bacteria outcompete methane producing bacteria for the common substrate H2. A similar competition may exist in human faeces where the methane (CH4) producing status of an individual depends on the faecal concentration of sulphate reducing bacteria. To determine if non-methanogenic faeces outcompete CH4 producing faeces for H2, aliquots of each type of faeces were incubated alone or mixed together, with or without addition of 10% H2 and/or 20 mmol/l sulphate. Methane producing faeces consumed H2 significantly more rapidly and reduced faecal H2 tension to a lower value compared with non-methanogenic faeces. The mixture of the two types of faeces yielded significantly more CH4 than CH4 producing faeces alone (mean (SD) 8.5 (1.3) v 2.9 (0.45) mmol/l of homogenate per 24 hours, p less than 0.01). Faecal sulphide concentrations were similar in CH4 producing and non-producing homogenates both before and after 24 hours of incubation. The addition of sulphate to the homogenates did not significantly influence CH4 production or sulphide formation. Our results suggest that in human faeces methane producing bacteria outcompete other H2 consuming bacteria for H2.